PERAN KOPERASI LUMINTU DALAM MENSEJAHTERAKAN SANTRI (Studi Kasus Pada Pondok Pesantren Bustanul Mansuriyah) - As'illah (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This research aims to explain the role of the Lumintu Cooperative in the welfare of the santri of the Bustanul Mansuriyah Islamic Boarding School. The method used is a qualitative method using a literature study and conducting interviews with informants. The results of this study are that Islamic Boarding School Cooperative (kopotren) basically plays an active role in the daily life of the santri. At the Bustanul Mansuriyah Islamic Boarding school, with the Islamic Boarding School Coperative (kopotren). The existence of the Lumintu Cooperative can provide a very beneficial role for the santri of the Bustanul Mansuriyah Islamic Boarding School. The santri certainly feel well-being as long as this cooperative exists with the provision of the basic needs of the santri. Not only welfare is the role of the cooperative, but there is entrepreneurial spirit training for santri and can improve the economy of the Bustanul Mansuriyah Islamic Boarding School. With the presence of this cooperative, they will no longer find it difficult to meet their needs while at the Islamic Boarding School. In running a cooperative, it is impossible to be separated from the influencing factors, as experienced by the guardians of this cooperative, namely the existence of supporting factors starting with the friendliness of the cooperative guards to the procedures for managing it and also the location of the place far from gril’s boarding school as an inhibiting factor. . However, the Coorperative Bustanul Mansuriyah Islamic Boarding School has implemented ways to overcome these factors by the cooperative guards.